Analysis of endovascular treatment of ruptured microaneurysms compared with ruptured larger aneurysms. (20th May 2015) - Murias Quintana, Eduardo; Vega, Pedro; Morales, Edison; Gil, Alberto; Cuellar, Hugo; Navia, Pedro; Saiz, Antonio; Meilán, Angela; Cadenas, Maria; Larrosa, Davinia; Gutierrez-Morales, Julio Cesar; Lopez, Antonio
Abstract : Objective: To retrospectively analyze the complications and outcome of the endovascular treatment of ruptured microaneurysms compared with the treatment of ruptured larger aneurysms. Methods: 40 ruptured cerebral microaneurysms treated by endovascular techniques were selected retrospectively and compared with 207 larger ruptured cerebral aneurysms treated by endovascular techniques during the same time period. Medical charts and imaging studies were reviewed to analyze baseline clinical and epidemiologic characteristics, procedural complications, and clinical outcomes Results: Cerebral microaneurysms had a higher incidence of intraoperative technical ruptures (13.5% vs 2.9%, p<0.005). The number of thromboembolic complications was not increased. Patient prognosis was similar for the two groups (mean modified Rankin Scale score 1.81 vs 2.09, p>0.1). Conclusions: Coiling of cerebral microaneurysms has a reasonable safety profile with good clinical outcomes, similar to coiling of larger aneurysms. In our experience, the systematic use of remodeling balloons, operator experience, and the ability to manage complications are the reasons for the satisfactory results.